Orbital and In‐Situ Investigation of Periodic Bedrock Ridges in Glen Torridon, Gale Crater, Mars. Issue 6 (26th May 2022) - Stack, Kathryn M.; Dietrich, William E.; Lamb, Michael P.; Sullivan, Robert J.; Christian, John R.; Newman, Claire E.; O'Connell‐Cooper, Catherine D.; Sneed, Jonathan W.; Day, Mackenzie; Baker, Mariah; Arvidson, Raymond E.; Fedo, Christopher M.; et al.
Abstract: Gale crater, the field site for NASA's Mars Science Laboratory Curiosity rover, contains a diverse and extensive record of aeolian deposition and erosion. This study focuses on a series of regularly spaced, curvilinear, and sometimes branching bedrock ridges that occur within the Glen Torridon region on the lower northwest flank of Aeolis Mons, the central mound within Gale crater. During Curiosity's exploration of Glen Torridon between sols ∼2300–3080, the rover drove through this field of ridges, providing the opportunity for in situ observation of these features. This study uses orbiter and rover data to characterize ridge morphology, spatial distribution, compositional and material properties, and association with other aeolian features in the area. Based on these observations, we find that the Glen Torridon ridges are consistent with an origin as wind‐eroded bedrock ridges, carved during the exhumation of Mount Sharp. Erosional features like the Glen Torridon ridges observed elsewhere on Mars, termed periodic bedrock ridges (PBRs), have been interpreted to form transverse to the dominant wind direction. The size and morphology of the Glen Torridon PBRs are consistent with transverse formative winds, but the orientation of nearby aeolian bedforms and bedrock erosional features raise the possibility of PBR formation by a net northeasterly wind regime. Although several formation models for the Glen Torridon PBRs are still under consideration, and questions persist about the nature of PBR‐forming paleowinds, the presence of PBRs at this site provides important constraints on the depositional and erosional history of Gale crater. Plain Language Summary: Wind has played a major role in sculpting the surface of Mars. Gale crater, the field site for NASA's Mars Science Laboratory Curiosity rover since it landed there in 2012, contains a vast and varied record of deposition and erosion by the wind. This study focuses on a series of regularly spaced, generally straight bedrock ridges that occur within the clay‐bearing Glen Torridon region of Aeolis Mons (informally named Mount Sharp) in Gale crater. During Curiosity's exploration of the Glen Torridon region between sols ∼2300–3080 of the mission, the rover drove through this field of ridges, acquiring images and compositional observations along the way. This study characterizes the Glen Torridon ridges using orbiter and rover data to determine their shape, size, occurrence, and relationship to other wind‐formed features in the area. We find that the Glen Torridon ridges were carved by wind into the bedrock of Mount Sharp. Questions remain about the winds that formed these ridges, but this study provides important information about the history and environment of Gale crater and reports the first rover observations of this type of erosional feature on Mars. Key Points: Decameter‐long, regularly spaced bedrock ridges oriented northeast‐southwest occur throughout the Glen Torridon region of Aeolis Mons Glen Torridon ridges cross‐cut elevation contours and bedding, exhibit bifurcations, and are disrupted by small impact craters Glen Torridon ridges are erosional periodic bedrock ridges whose formation places erosional and depositional constraints on Aeolis Mons